System identification of energy dissipation in a mechanical model undergoing high velocities: An indirect use of perpetual points. (August 2018) - Brzeski, P.; Virgin, L.N.
Highlights: We developed a procedure for the identification of energy dissipation based on perpetual points. The advantages of the method are presented basing on the simple pendulum system. The method allows easy comparison between the accuracy of different energy dissipation models. Proposed approach is validated by comparing numerically optimized models with the experimental data. Abstract: Energy dissipation is often the most challenging component of system identification in the modeling of dynamical behavior in mechanical systems. Even for a relatively simple single-degree-of-freedom system such as the rigid-arm pendulum, it can be difficult to choose the form of the best damping model, as well as the subsequent challenge of estimating the appropriate parameters, especially for a model that accurately captures the nature of energy dissipation over a wide range of operational conditions. This paper specifically focuses on a mechanical system in which subtle changes can be made to the system with a view to isolating and modeling energy dissipation. The approach described in this paper was developed as a by-product of experimentally investigating perpetual points. It is shown that certain features of high-velocity, spinning motion lends itself to greater fidelity in the data-fitting process and thus added confidence in choosing the most accurate energy dissipation model with the most appropriate parameters.